2012
DOI: 10.1175/waf-d-11-00130.1
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Satellite Imagery for Real-Time High-Resolution Model Evaluation

Abstract: Output from a real-time high-resolution numerical model is used to generate synthetic infrared satellite imagery. It is shown that this imagery helps to characterize model-simulated large-scale precursors to the formation of deep-convective storms as well as the subsequent development of storm systems. A strategy for using this imagery in the forecasting of severe convective weather is presented. This strategy involves comparing model-simulated precursors to their observed counterparts to help anticipate model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…The SOI code accounts for the assumptions made by the microphysics schemes, including each species' particle density, slope intercept parameter, and particle size distribution (e.g., MarshallPalmer, generalized gamma). Previous studies have shown that the SOI model produces accurate brightness temperatures in both clear and cloudy conditions (e.g., Otkin and Greenwald 2008;Otkin et al 2009;Bikos et al 2012) and the accuracy is expected to be within 1 K for infrared brightness temperatures (Otkin 2010).…”
Section: Synthetic Satellite Data and Forward Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOI code accounts for the assumptions made by the microphysics schemes, including each species' particle density, slope intercept parameter, and particle size distribution (e.g., MarshallPalmer, generalized gamma). Previous studies have shown that the SOI model produces accurate brightness temperatures in both clear and cloudy conditions (e.g., Otkin and Greenwald 2008;Otkin et al 2009;Bikos et al 2012) and the accuracy is expected to be within 1 K for infrared brightness temperatures (Otkin 2010).…”
Section: Synthetic Satellite Data and Forward Model Descriptionmentioning
confidence: 99%
“…The model-to-satellite approach has been used to validate and improve the accuracy of cloud microphysics schemes (Grasso and Greenwald 2004;Chaboureau and Pinty 2006;Otkin and Greenwald 2008;Grasso et al 2010;Jankov et al 2011). Synthetic satellite radiances derived from high-resolution NWP models have also been used as a proxy for future satellite sensors (Otkin et al 2007;Grasso et al 2008;Feltz et al 2009) and have been shown to be a valuable forecast tool at convective scales (Bikos et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been used for wide variety of model evaluation studies [Morcrette, 1991;Chevallier and Kelly, 2002;Cintineo et al, 2014; and others described in section 1]. Recently, operational and forecasting research centers start producing simulated satellite IR images from highresolution mesoscale modeling, and the simulated satellite fields are available in real time and utilized by forecasters [Clark et al, 2012;Bikos et al, 2012].…”
Section: Modeling Systemsmentioning
confidence: 99%
“…More recent advances in computing resources have led to the development of more computationally expensive model-derived fields such as synthetic satellite imagery and simulated radar reflectivity [e.g., Chevallier et al (2001); Chevallier and Kelly (2002); Otkin and Greenwald (2008); Bikos et al (2012)]. Recent increases in temporal and spatial resolution of numerical weather prediction (NWP) model simulations and advances in the post-processing of the NWP output can result in simulations that realistically depict the spatial characteristics of the observed cloud features (Lee et al 2014).…”
Section: A Backgroundmentioning
confidence: 99%